Μελέτη οξείας τοξικότητας σε καρκινοειδή οργανισμούς, χρόνιας τοξικότητας σε φυτά και οιστρογονικότητας της λουπανίνης - Ζαχαρία, Ειρήνη (Τμήμα Επιστήμης και Τεχνολογίας Περιβάλλοντος, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2017)
This research aims to determine the toxicity of several concentrations of lupanine on Vibrio fischeri , Daphnia magna and the plants Sinapis alba and Sorghum saccharatum. The estrogenicity of the compound was also studied in the genetically modified yeast Saccharomyces cerevisiae. V. fischeri, D. magna, S. alba and S. saccharatum represent a specific environment (eg soil, fresh water, etc.) and we used them to study the toxicological effect of lupanine, when released into the environment. Due to the lack of similar experiments focusing on the toxic effects of the compounds in water bodies and the soil, the information provided in the current study can be significant. The lupanine which used in the study was proceed from Lupinus albus. The experiment on Vibrio fischeri was based on the reduction of the bacterial bioluminescence in the presence of the toxic substance. The exposure period was 5 and 15 minutes before measuring the bioluminescence by using the luminometer. Afterwards the EC50 was calculated for each exposure period. The results from the acute toxicity measurements of the bacterium were 89 mg/L after 5 minutes and after 15 minutes 47 mg/L. Acute toxicity on Daphnia magna was also studied. The exposure period was 24 and 48 hours, for each the EC50 was calculated by estimating the immobilization of the organism with the results being 60 mg/L and 12 mg/L after 24 and 48 hours of exposure, respectively. The plants Sorghum saccharatum (monocotyledon) and Sinapis alba (dicotyledonous) were also used as biomarkers regarding their growth inhibition, that was monitored based on the length of roots, as well as the germination index given as the number of germinated seeds, as the endpoints. The measurements were taken after 96 hours of exposure and the concentrations of exposure were 100 mg/L - 6.25 mg/L. Subsequently, growth inhibition was correlated to lupanine concentration and the corresponding EC50 values were calculated. The results showed that lupanine had a positive effect on the growth of the dicotyledonous S.alba. Lupanine severely impacted the root growth of S. saccharatum demonstrating inhibition that ranged between 97 and 99.7% for the four highest alkaloid concentrations employed (100, 50, 25 and 12.5 mg/L). The alkaloid also inhibited the germination of S. saccharatum (40-80%) in the four highest concentrations tested. In the last experiment, was studied the effect of lupanine on estrogenicity with S. cerevisiae. Unfortunately, no estrogenicity was observed which was associated with possible infection of the used yeast, which was found by the study of yeast samples by PCR. Based on the results, lupanine was observed except for S. alba, with the result that when exposed to the environment it has negative consequences. However, it is proposed to further study environmental organisms for lupanine and sparteine, since sparteine is considered to be more toxic than lupanine through study results. It is also proposed to further study the effect of lupanine on estrogenicity since no results have been found through this study.
Keywords: Lupanine; Vibrio fischeri; Daphnia magna; Sinapis alba; Sorghum saccharatum; Saccharomyces cerevisiae; Estrogenicity; Λουπανίνη; Οιστρογονικότητα